Borosilicate glass with high ultraviolet isolation performance and suitable for drug packaging and preparation method thereof
By optimizing the formula and process of borzanicate glass, increase specific oxides and use specific melting agents and clarification agents, solve the problem of poor anti -ultraviolet performance of borosilicate glass, and achieve high ultraviolet blocking and good transparency The balance of the glass has improved the heat and chemical stability of the glass, and is suitable for drug packaging.
Patent Information
- Application Number
- CN202411651127.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing borosilicate glass used in drug packaging has poor UV resistance and insufficient thermal stability and chemical resistance, resulting in drugs being susceptible to UV light and may be contaminated.
By optimizing the formula of borosilicate glass, increasing the content of oxides such as tungsten trioxide, molybdenum oxide, cerium oxide, titanium dioxide, and bismuth trioxide, and using tungstate, cerium oxide molybdate, and bismuth titanate as fluxes , combined with tin oxide, sodium stannate, and phytate as compound clarifiers, to control the melting process to improve the UV isolation performance and transparency of the glass.
A balance of high -ultraviolet blocking performance and good visible light transmission rate, which improves the thermal stability of the glass and the stability of chemical resistance. It is suitable for drug packaging to ensure the quality and safety of the drug.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to borosilicate glass with high ultraviolet isolation performance and suitable for drug packaging and a preparation method thereof, belonging to the technical field of glass production. Background Art
[0002] Glass for drug packaging is bright and transparent, easy to disinfect, resistant to corrosion, resistant to high temperatures, and has good sealing properties. It is still the preferred packaging for common infusions, antibiotics, general powders, freeze-dried products, vaccines, blood, and biological preparations. Among the many different types of glass, borosilicate glass has excellent glass network integrity and density due to its high content of SiO2 and B2O3. Therefore, compared with other types of glass, borosilicate glass has better chemical stability, light transmittance, heat resistance, and mechanical stability. Based on the above characteristics, borosilicate glass has been widely used in the field of drug packaging. There is a requirement for transparency in pharmaceutical glass packaging. The high light transmittance of borosilicate glass gives it the advantage of good transparency, but this also means that a large part of the light in the pharmaceutical glass can irradiate the medicine, especially the ultraviolet light, which has a greater impact on the quality of the medicine. Therefore, when borosilicate glass is used for medicine, high anti-ultraviolet performance is required. The current method of blocking ultraviolet rays is mainly to use brown, tea or amber borosilicate glass. The above-mentioned non-transparent colored glass generally has a high content of iron compounds, which can easily cause the chemical resistance of borosilicate glass to decrease, which in turn can easily lead to contamination of the medicine. Therefore, the market is in urgent need of transparent borosilicate glass with good UV resistance for pharmaceutical packaging.
[0003] Chinese patent CN101591140A discloses a borosilicate glass for drug packaging with UV isolation performance, specifically relates to a borosilicate glass for drug packaging, the borosilicate glass has a transmittance τ greater than 80% in the visible range of light with a wavelength of 400nm, and a transmittance τ of up to 0.1% in the ultraviolet region below 260nm, each sample has a thickness of 1mm, a transition temperature Tg of 550℃ to 590℃, and a processing temperature VA of 1100℃ to 1200℃. The glass has the following composition in terms of weight % based on oxides: SiO2, 60~80; B2O3, 5~15; Al2O3, 2~10; TiO2, 0.5~7; ∑Li2O+K2O+Na2O, 3~10; ∑alkaline earth metal oxides, 0.5~10; ZrO2, 0~3; and Fe2O3, 0~0.2. The borosilicate glass used for drug packaging obtained in this patent has a transmittance of 0.1% at a wavelength of 260nm, which can only be achieved in one embodiment. The cut-off wavelengths of other embodiments and comparative examples when the transmittance is 0.1% are much larger than 260nm, and the anti-ultraviolet effect is not particularly ideal. Moreover, the linear thermal expansion coefficient of the borosilicate glass obtained in this patent is relatively large, and the thermal stability is not very good.
[0004] Chinese patent CN114292022A discloses an anti-ultraviolet and alkali-resistant borosilicate glass and its application. Its composition is based on oxides and contains the following components by weight fraction (wt%): TiO2 2.0~5.0wt%, CeO2 0.25~2.5wt% and Y2O3 0.25~3.0wt%, and does not contain iron compounds such as ferric oxide; the glass has good anti-ultraviolet performance, alkali resistance and good light transmittance, and is particularly suitable for use in the field of pharmaceutical packaging materials. The anti-ultraviolet and alkali-resistant borosilicate glass obtained in this patent has a transmittance of more than 5% under ultraviolet light with a wavelength of 380nm, which shows that its anti-ultraviolet performance is not particularly good.
[0005] From the above, we can see that the borosilicate glass currently used for drug packaging does not have particularly excellent UV resistance. Therefore, developing a borosilicate glass for drug packaging with high UV isolation performance is of great practical significance to the pharmaceutical industry. Summary of the invention
[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a borosilicate glass with high UV shielding performance and suitable for drug packaging and a preparation method thereof, so as to achieve the following invention objectives: to prepare borosilicate glass for drug packaging with high UV shielding performance.
[0007] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0008] A borosilicate glass having high ultraviolet light isolation performance and suitable for drug packaging and a preparation method thereof, wherein the specific formula of the borosilicate glass having high ultraviolet light isolation performance and suitable for drug packaging is, in parts by weight:
[0009] 70-95 parts of silicon dioxide,
[0010] Boron trioxide 25-35 parts,
[0011] 7-11 parts of sodium oxide,
[0012] 5~10 parts of aluminum oxide,
[0013] 3~8 parts of composite flux,
[0014] 1~4 parts of composite clarifier;
[0015] The composite flux is composed of tungstate, cerium oxymolybdate and bismuth titanate;
[0016] The tungstate is one of potassium tungstate, sodium tungstate, magnesium tungstate, lithium tungstate and aluminum tungstate;
[0017] The mass ratio of the tungstate, cerium oxide molybdate, and bismuth titanate is 20-60:25-50:10-60;
[0018] The composite clarifier is composed of tin oxide, sodium stannate and phytate;
[0019] The phytate is one of magnesium phytate, calcium phytate, sodium phytate, potassium phytate and zinc phytate;
[0020] The mass ratio of tin oxide, sodium stannate and phytate is 25-50:5-18:30-64;
[0021] The following are further improvements to the above technical solution:
[0022] The preparation method of the borosilicate glass with high ultraviolet isolation performance and suitable for drug packaging is as follows: according to the specific formula of the borosilicate glass with high ultraviolet isolation performance and suitable for drug packaging in parts by weight, corresponding masses of powdered raw materials such as silicon dioxide, diboron trioxide, sodium oxide, aluminum trioxide, composite flux, and composite clarifier are weighed, the powders are preliminarily mixed, and then put into a zirconia crucible, and then the temperature is raised to 1100-1350°C at a rate of 2-5°C / min and kept warm for 20-40 minutes, and then the temperature is raised to 1-3°C / min at a rate of 1-3°C / min. in, and then cool to 1700-1830°C and keep warm for 1-2.5 hours, then cool to 1450-1580°C and keep warm for 20-35 minutes, then pour the 1450-1580°C glass liquid into the graphite mold for molding, preheat the graphite mold to 900-1100°C in advance, maintain the temperature of 900-1100°C for annealing, after annealing for 1-2.5 hours, cool to room temperature at a rate of 1-2°C / min, polish the surface after demolding, and obtain borosilicate glass with high UV isolation performance and suitable for drug packaging.
[0023] Compared with the prior art, the present invention achieves the following beneficial effects:
[0024] 1. The borosilicate glass obtained by the present invention has high ultraviolet light blocking performance and good visible light transmittance, which fully meets the characteristic requirements of glass for pharmaceutical packaging that can both shield ultraviolet light and allow visible light to penetrate. The high ultraviolet light blocking performance and the selective penetration of visible light are mainly achieved by the oxides such as tungsten trioxide, molybdenum oxide, cerium oxide, titanium dioxide and bismuth trioxide incorporated into the borosilicate glass network. By optimizing the proportion content, raw material source, melting process control and high-efficiency composite clarifier of the above oxides, the balance between transparency and ultraviolet light blocking performance is taken into account, and finally a borosilicate glass suitable for pharmaceutical packaging with high transmittance under visible light and extremely low ultraviolet light transmittance, excellent thermal stability and chemical resistance is prepared;
[0025] 2. The borosilicate glass obtained by the present invention contains tungsten trioxide, molybdenum oxide, cerium oxide, titanium dioxide and bismuth trioxide in its glass network, which are generated by thermal decomposition of three flux components, namely tungstate, cerium oxide molybdate and bismuth titanate. Firstly, the melting points of tungstate, cerium oxide molybdate and bismuth titanate are relatively low, and the viscosity of the liquid obtained after melting is relatively low, which can effectively reduce the melting temperature of the two main materials, silicon dioxide and boron trioxide, and the viscosity of the molten liquid obtained after melting into a liquid state, and play a role in fluxing and improving fluidity. In addition, the decomposition products obtained by thermal decomposition of tungstate, cerium oxide molybdate and bismuth titanate are all oxides required in the glass network, and no other impurities are introduced. Therefore, the above three flux components do not affect the thermal stability and chemical resistance of borosilicate glass while improving the ultraviolet shielding performance and visible light transmittance of borosilicate glass. The test data disclosed in the present invention also proves this point;
[0026] 3. The composite clarifier used in the present invention is composed of three components: tin oxide, sodium stannate, and phytate. Among them, tin oxide is a relatively common glass clarifier. It mainly promotes the melting and growth of tiny bubbles by reducing the viscosity of the glass melt and decomposing to generate oxygen, so as to promote the rapid discharge of bubbles. The clarification principle of sodium stannate is similar to that of tin oxide. In the glass melt, the melting viscosity of sodium stannate is lower, and after reaching a higher melting temperature, sodium stannate will first decompose to generate tin oxide, which will promote the content of tin oxide in the high-temperature stage, so as to maintain the decomposition rate of tin oxide at a high state, maintain the oxygen content generated by the decomposition in the glass melt, so as to promote the melting and discharge of more tiny bubbles in the high-temperature stage. The phytate added to the composite clarifier also utilizes its characteristics of being easy to decompose and generate a large amount of gas at high temperature, so as to play the effect of strong stirring of the high-temperature melt, accelerate the rapid aggregation and growth of extremely fine bubbles in the glass melt, promote these fine bubbles to escape quickly and smoothly from the inside of the melt, and ensure that the glass melt obtains a better clarification effect;
[0027] 4. The borosilicate glass obtained by the present invention has high ultraviolet isolation performance and is suitable for drug packaging, and the linear thermal expansion coefficient is 3.34~3.54×10 -6 / K, water resistance 0.01~0.04mL, alkali resistance 40~46mg / dm 2 , acid resistance 0.31~0.45mg / dm 2 The corresponding transmittances at wavelengths of 260nm, 300nm, 360nm, 400nm, and 440nm are 0.01~0.04%, 0.03~0.06%, 0.07~0.10%, 0.16~0.22%, and 68.56~70.25%, respectively. DETAILED DESCRIPTION
[0028] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0029] Example 1: A method for preparing borosilicate glass with high ultraviolet shielding performance and suitable for drug packaging
[0030] The specific formula of the borosilicate glass having high ultraviolet isolation performance and suitable for drug packaging is, in parts by weight:
[0031] 80 parts of silicon dioxide,
[0032] 30 parts of boron trioxide,
[0033] 9 parts of sodium oxide,
[0034] 8 parts of aluminum oxide,
[0035] 6 parts of composite flux,
[0036] 3 parts of composite clarifier;
[0037] The composite flux is composed of tungstate, cerium oxymolybdate and bismuth titanate;
[0038] The tungstate is potassium tungstate;
[0039] The mass ratio of the tungstate, cerium oxymolybdate, and bismuth titanate is 45:35:40;
[0040] The composite clarifier is composed of tin oxide, sodium stannate and phytate;
[0041] The phytate is magnesium phytate;
[0042] The mass ratio of tin oxide, sodium stannate and phytate is 35:11:50;
[0043] According to the specific formula of borosilicate glass with high UV isolation performance and suitable for drug packaging in parts by weight, corresponding masses of powdered raw materials such as silicon dioxide, boron trioxide, sodium oxide, aluminum trioxide, composite flux, composite clarifier, etc. are weighed, these powders are preliminarily mixed, and then put into a zirconia crucible, and then the temperature is increased to 1250°C at a rate of 4°C / min and kept warm for 30 minutes, then the temperature is increased to 1780°C at a rate of 2°C / min and kept warm for 2 hours, then the temperature is reduced to 1540°C and kept warm for 30 minutes, and then the 1540°C glass liquid is poured into a graphite mold for molding, the graphite mold is preheated to 1000°C in advance, and the temperature is maintained at 1000°C for annealing. After annealing for 2 hours, the temperature is reduced to room temperature at a rate of 1.6°C / min, and the surface is polished after demolding to obtain borosilicate glass with high UV isolation performance and suitable for drug packaging.
[0044] Example 2: A method for preparing borosilicate glass with high ultraviolet shielding performance and suitable for drug packaging
[0045] The specific formula of the borosilicate glass having high ultraviolet isolation performance and suitable for drug packaging is, in parts by weight:
[0046] 70 parts of silicon dioxide,
[0047] 25 parts of boron trioxide,
[0048] 7 parts of sodium oxide,
[0049] 5 parts of aluminum oxide,
[0050] 3 parts of composite flux,
[0051] 1 part of composite clarifier;
[0052] The composite flux is composed of tungstate, cerium oxymolybdate and bismuth titanate;
[0053] The tungstate is sodium tungstate;
[0054] The mass ratio of the tungstate, cerium oxide molybdate, and bismuth titanate is 20:25:10;
[0055] The composite clarifier is composed of tin oxide, sodium stannate and phytate;
[0056] The phytate is calcium phytate;
[0057] The mass ratio of tin oxide, sodium stannate and phytate is 25:5:30;
[0058] According to the specific formula of borosilicate glass with high UV isolation performance and suitable for drug packaging in parts by weight, corresponding masses of powdered raw materials such as silicon dioxide, boron trioxide, sodium oxide, aluminum trioxide, composite flux, composite clarifier, etc. are weighed, these powders are preliminarily mixed, and then put into a zirconia crucible, and then the temperature is increased to 1100°C at a rate of 2°C / min and kept warm for 20 minutes, then the temperature is increased to 1700°C at a rate of 1°C / min and kept warm for 1 hour, then the temperature is reduced to 1450°C and kept warm for 20 minutes, and then the 1450°C glass liquid is poured into a graphite mold for molding, the graphite mold is preheated to 900°C in advance, and the temperature is maintained at 900°C for annealing. After annealing for 1 hour, the temperature is reduced to room temperature at a rate of 1°C / min, and the surface is polished after demolding to obtain borosilicate glass with high UV isolation performance and suitable for drug packaging.
[0059] Example 3: A method for preparing borosilicate glass with high ultraviolet shielding performance and suitable for drug packaging
[0060] The specific formula of the borosilicate glass having high ultraviolet isolation performance and suitable for drug packaging is, in parts by weight:
[0061] 95 parts of silicon dioxide,
[0062] 35 parts of boron trioxide,
[0063] 11 parts of sodium oxide,
[0064] 10 parts of aluminum oxide,
[0065] 8 parts of composite flux,
[0066] 4 parts of composite clarifier;
[0067] The composite flux is composed of tungstate, cerium oxymolybdate and bismuth titanate;
[0068] The tungstate is magnesium tungstate;
[0069] The mass ratio of the tungstate, cerium oxymolybdate, and bismuth titanate is 60:50:60;
[0070] The composite clarifier is composed of tin oxide, sodium stannate and phytate;
[0071] The phytate is sodium phytate;
[0072] The mass ratio of tin oxide, sodium stannate and phytate is 50:18:64;
[0073] According to the specific formula of borosilicate glass with high UV isolation performance and suitable for drug packaging in parts by weight, corresponding masses of powdered raw materials such as silicon dioxide, boron trioxide, sodium oxide, aluminum trioxide, composite flux, composite clarifier, etc. are weighed, these powders are preliminarily mixed, and then put into a zirconia crucible, and then the temperature is increased to 1350°C at a rate of 5°C / min and kept warm for 40 minutes, then the temperature is increased to 1830°C at a rate of 3°C / min and kept warm for 2.5 hours, and then the temperature is reduced to 1580°C and kept warm for 35 minutes, and then the 1580°C glass liquid is poured into a graphite mold for molding, the graphite mold is preheated to 1100°C in advance, and the temperature is maintained at 1100°C for annealing. After annealing for 2.5 hours, the temperature is cooled to room temperature at a rate of 2°C / min, and the surface is polished after demolding, so as to obtain borosilicate glass with high UV isolation performance and suitable for drug packaging.
[0074] Example 4: A method for preparing borosilicate glass with high ultraviolet shielding performance and suitable for drug packaging
[0075] The specific formula of the borosilicate glass having high ultraviolet isolation performance and suitable for drug packaging is, in parts by weight:
[0076] 70 parts of silicon dioxide,
[0077] 25 parts of boron trioxide,
[0078] 7 parts of sodium oxide,
[0079] 5 parts of aluminum oxide,
[0080] 3 parts of composite flux,
[0081] 1 part of composite clarifier;
[0082] The composite flux is composed of tungstate, cerium oxymolybdate and bismuth titanate;
[0083] The tungstate is lithium tungstate;
[0084] The mass ratio of the tungstate, cerium oxide molybdate, and bismuth titanate is 20:25:10;
[0085] The composite clarifier is composed of tin oxide, sodium stannate and phytate;
[0086] The phytate is potassium phytate;
[0087] The mass ratio of tin oxide, sodium stannate and phytate is 25:5:30;
[0088] According to the specific formula of borosilicate glass with high UV isolation performance and suitable for drug packaging in parts by weight, corresponding masses of powdered raw materials such as silicon dioxide, boron trioxide, sodium oxide, aluminum trioxide, composite flux, composite clarifier, etc. are weighed, these powders are preliminarily mixed, and then put into a zirconia crucible, and then the temperature is increased to 1100°C at a rate of 2°C / min and kept warm for 20 minutes, then the temperature is increased to 1700°C at a rate of 1°C / min and kept warm for 1 hour, then the temperature is reduced to 1450°C and kept warm for 20 minutes, and then the 1450°C glass liquid is poured into a graphite mold for molding, the graphite mold is preheated to 900°C in advance, and the temperature is maintained at 900°C for annealing. After annealing for 1 hour, the temperature is reduced to room temperature at a rate of 1°C / min, and the surface is polished after demolding to obtain borosilicate glass with high UV isolation performance and suitable for drug packaging.
[0089] Example 5: A method for preparing borosilicate glass with high ultraviolet shielding performance and suitable for drug packaging
[0090] The specific formula of the borosilicate glass having high ultraviolet isolation performance and suitable for drug packaging is, in parts by weight:
[0091] 95 parts of silicon dioxide,
[0092] 35 parts of boron trioxide,
[0093] 11 parts of sodium oxide,
[0094] 10 parts of aluminum oxide,
[0095] 8 parts of composite flux,
[0096] 4 parts of composite clarifier;
[0097] The composite flux is composed of tungstate, cerium oxymolybdate and bismuth titanate;
[0098] The tungstate is aluminum tungstate;
[0099] The mass ratio of the tungstate, cerium oxymolybdate, and bismuth titanate is 60:50:60;
[0100] The composite clarifier is composed of tin oxide, sodium stannate and phytate;
[0101] The phytate is zinc phytate;
[0102] The mass ratio of tin oxide, sodium stannate and phytate is 50:18:64;
[0103] According to the specific formula of borosilicate glass with high UV isolation performance and suitable for drug packaging in parts by weight, corresponding masses of powdered raw materials such as silicon dioxide, boron trioxide, sodium oxide, aluminum trioxide, composite flux, composite clarifier, etc. are weighed, these powders are preliminarily mixed, and then put into a zirconia crucible, and then the temperature is increased to 1350°C at a rate of 5°C / min and kept warm for 40 minutes, then the temperature is increased to 1830°C at a rate of 3°C / min and kept warm for 2.5 hours, and then the temperature is reduced to 1580°C and kept warm for 35 minutes, and then the 1580°C glass liquid is poured into a graphite mold for molding, the graphite mold is preheated to 1100°C in advance, and the temperature is maintained at 1100°C for annealing. After annealing for 2.5 hours, the temperature is cooled to room temperature at a rate of 2°C / min, and the surface is polished after demolding, so as to obtain borosilicate glass with high UV isolation performance and suitable for drug packaging.
[0104] Comparative Example 1: Based on Example 1, no tungstate is added to the composite flux, and 45 parts of tungstate are replaced by 45 parts of cerium oxide molybdate. The specific operation is as follows:
[0105] The 45 parts of tungstate were replaced by 45 parts of cerium oxide molybdate, and the other operations were the same as in Example 1.
[0106] Comparative Example 2: Based on Example 1, cerium oxide molybdate was not added to the composite flux, and 35 parts of cerium oxide molybdate were replaced by 35 parts of tungstate. The specific operation was as follows:
[0107] 35 parts of cerium oxide molybdate were replaced by 35 parts of tungstate, and the other operations were the same as in Example 1.
[0108] Comparative Example 3: Based on Example 1, bismuth titanate was not added to the composite flux, and 40 parts of bismuth titanate were replaced by 40 parts of tungstate. The specific operation was as follows:
[0109] 40 parts of bismuth titanate were replaced by 40 parts of tungstate, and other operations were the same as in Example 1.
[0110] Comparative Example 4: Based on Example 1, sodium stannate was not added to the composite clarifier, and 11 parts of sodium stannate were replaced by 11 parts of tin oxide. The specific operation was as follows:
[0111] The 11 parts of sodium stannate were replaced by 11 parts of tin oxide, and the other operations were the same as in Example 1.
[0112] Comparative Example 5: Based on Example 1, no phytate was added to the composite clarifier, and 50 parts of phytate were replaced by 50 parts of tin oxide. The specific operation was as follows:
[0113] The remaining steps were the same as in Example 1 except that 50 parts of phytate were replaced by 50 parts of tin oxide.
[0114] Performance Test:
[0115] The borosilicate glass obtained in Examples 1, 2, 3, 4, 5 and Comparative Examples 1, 2, 3, 4, 5 and having high ultraviolet isolation performance and suitable for drug packaging was tested for the following performance indicators:
[0116] 1. Linear thermal expansion coefficient test: Determined according to ASTM E228-2017 "Test method for linear thermal expansion coefficient of solid materials using push rod dilatometer";
[0117] 2. Water resistance test: According to the water resistance test method in YBB00362004-2015, take a certain amount of glass particles of specified size, put them in a specified container, add a certain amount of water, and heat them under specified conditions. By titrating the leaching solution, the volume of hydrochloric acid titration solution (0.01mol / L) consumed per gram of glass particles is used to measure the degree of water erosion of the glass particles and grade them. The maximum value of high chemical resistance glass belonging to HGB1 water resistance is 0.10mL, the maximum value of glass belonging to HGB2 water resistance is 0.20mL, and the maximum value of glass belonging to HGB3 water resistance is 0.85mL;
[0118] 3. Alkali resistance test: According to the alkali resistance test method in YBB00352004-2015, the total surface area is 10cm 2 ~15cm 2The glass sample is etched with a boiling mixed solution of equal volumes of 0.5 mol / L sodium carbonate and 1.0 mol / L sodium hydroxide for 3 hours. The mass lost per unit surface area of the glass sample is measured. The maximum weight loss of Class 1 alkali-resistant glass is 75 mg / dm 2 The maximum weight loss of Class 2 alkali-resistant glass is 175 mg / dm 2 , greater than 175 mg / dm 2 It is level 3 alkali resistant;
[0119] 4. Acid resistance test: According to the acid resistance test method in YBB00342004-2015, the 2 The glass sample is etched in a boiling 6±0.2mol / L hydrochloric acid solution for 6 hours, and the mass loss per unit area is measured. The maximum weight loss of grade 1 acid-resistant glass is 0.7mg / dm 2 The maximum weight loss of glass belonging to grade 2 acid resistance is 1.5 mg / dm 2 , greater than 1.5 mg / dm 2 It is grade 3 acid resistant;
[0120] 5. Test of UV-visible light transmittance (T%): First, use a micro-controlled internal circular cutting machine to cut the glass block into glass sheets with a thickness of 1.5±0.1mm, then use a precision grinding and polishing machine to grind both sides of the glass sheet into a mirror surface, and the thickness of the glass sheet is 1±0.05mm. Finally, use a UV-visible spectrophotometer to measure the transmittance under different wavelengths of light;
[0121] The above index test data are shown in Table 1:
[0122] Table 1
[0123]
[0124] From the data in Table 1, it can be seen that the linear thermal expansion coefficients of the eight samples in Examples 1-5 and Comparative Examples 1-3 are all within 3.7×10 -6 / K or less, the water resistance is all at HGB1 level, and the alkali resistance and acid resistance are all at level 1, which indicates that the thermal properties, hydrolysis resistance and chemical resistance of the borosilicate glasses obtained in Examples 1-5 and Comparative Examples 1-3 are relatively excellent. It also indicates that the three components of tungstate, cerium oxymolybdate and bismuth titanate contained in the flux can ensure a good fluxing effect when any two of the three components exist. However, the light transmittance of Comparative Examples 1-3 at different wavelengths is very different from that of Example 1. The light transmittance of Comparative Example 1 under ultraviolet light in the wavelength range of 260~400nm and visible light at a wavelength of 440nm is much greater than that of Example 1. If tungstate is not added to Comparative Example 1, the borosilicate glass corresponding to Comparative Example 1 does not contain tungsten trioxide. The transmittance data show that tungsten trioxide not only has a very strong shielding effect on ultraviolet rays, but also has a certain shielding effect on visible light. The amount of tungstate added in Comparative Examples 2 and 3 is much greater than that in Example 1. The transmittance of these two examples under ultraviolet light in the wavelength range of 260~400nm and under visible light at a wavelength of 440nm are less than or equal to that of Example 1, especially the transmittance under visible light at a wavelength of 440nm. Comparative Examples 2 and 3 are much less than that of Example 1. Considering that the amount of tungstate added in Comparative Example 3 is 5 more than that in Comparative Example 2, this shows that the tungsten trioxide finally generated by tungstate not only provides a very strong ultraviolet shielding effect but also plays a role in shielding visible light. Moreover, as the amount of tungstate increases, the amount of tungsten trioxide increases accordingly, and the shielding effects of ultraviolet light and visible light increase accordingly. In the composite clarifier of Comparative Example 4, sodium stannate is not added. Compared with Example 1, the linear thermal expansion coefficient, water resistance, alkali resistance and acid resistance of Comparative Example 4 are greatly reduced. The transmittance of Comparative Example 4 under ultraviolet light in the wavelength range of 260-300nm is greater than that of Example 1, and the transmittance under ultraviolet light in the wavelength range of 360-400nm and the transmittance under visible light at a wavelength of 440nm are worse than those of Example 1. This shows that the composite clarifier without sodium stannate has a relatively poor clarification effect on borosilicate glass, which will lead to a decrease in the transparency of the glass, and further greatly reduce the shielding effect of borosilicate glass on near-ultraviolet light with a shorter wavelength and the transmission effect of visible light. The situation of Comparative Example 5 is similar to that of Comparative Example 4, and the linear thermal expansion coefficient, water resistance, alkali resistance and acid resistance of Comparative Example 5 are reduced more than those of Example 1, which shows that the influence of phytate on the clarification effect is greater than that of sodium stannate.
[0125] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A borosilicate glass having high ultraviolet light isolation performance and suitable for drug packaging, characterized in that: The specific formula of the borosilicate glass having high ultraviolet isolation performance and suitable for drug packaging is, in parts by weight: 70-95 parts of silicon dioxide, Boron trioxide 25-35 parts, 7-11 parts of sodium oxide, 5~10 parts of aluminum oxide, 3~8 parts of composite flux, 1~4 parts of composite clarifier; The composite flux is composed of tungstate, cerium oxymolybdate and bismuth titanate; The tungstate is one of potassium tungstate, sodium tungstate, magnesium tungstate, lithium tungstate and aluminum tungstate; The composite clarifier is composed of tin oxide, sodium stannate and phytate; The phytate is one of magnesium phytate, calcium phytate, sodium phytate, potassium phytate and zinc phytate.
2. The borosilicate glass with high ultraviolet shielding performance and suitable for drug packaging according to claim 1, characterized in that: The mass ratio of the tungstate, cerium oxymolybdate and bismuth titanate is 20-60:25-50:10-60.
3. The borosilicate glass with high ultraviolet shielding performance and suitable for drug packaging according to claim 1, characterized in that: The mass ratio of the tin oxide, sodium stannate and phytate is 25-50:5-18:30-64.
4. The method for preparing borosilicate glass having high ultraviolet light shielding performance and suitable for drug packaging according to claim 1, characterized in that: According to the specific formula of borosilicate glass with high UV isolation performance and suitable for drug packaging, the corresponding mass of silicon dioxide, boron trioxide, sodium oxide, aluminum trioxide, composite flux, and composite clarifier are weighed, and these powdered raw materials are preliminarily mixed and placed in a zirconia crucible, and then heated to 1100~1350℃ at a rate of 2~5℃ / min and kept warm for 20~40 minutes, and then heated to 1700~1830℃ at a rate of 1~3℃ / min And keep it warm for 1~2.5 hours, then cool it to 1450~1580℃ and keep it warm for 20~35 minutes, then pour the 1450~1580℃ glass liquid into the graphite mold for molding, preheat the graphite mold to 900~1100℃ in advance, maintain the temperature of 900~1100℃ for annealing, after annealing for 1~2.5 hours, cool it to room temperature at a rate of 1~2℃ / min, polish the surface after demolding, and obtain borosilicate glass with high UV isolation performance and suitable for drug packaging.
Citation Information
Patent Citations
Borosilicate glass with uv-blocking properties for pharmaceutical packaging
CN101591140A
Anti-ultraviolet alkali-resistant borosilicate glass and application thereof
CN114292022A
Borosilicate glass suitable for electric light source
CN101428966A
Borosilicate glass tube for photo-thermal power generation
CN101838106A